Determination of selected neurotransmitter metabolites using monolithic column chromatography coupled with chemiluminescence detection - Adcock, J.; Barnett, N.; Costin, J.; Francis, P.; Lewis, Simon (Elsevier, 2005)
The oxidation of selected clinically important neurotransmitter metabolites with acidic potassium permanganate in the presence of polyphosphates evokes chemiluminescence of sufficient intensity to enable the sensitive determination of these species. Limits of detection for 5-hydroxyindole-3-acetic acid (5-HIAA), vanilmandelic acid (VMA; ,4-dihydroxy-3-methoxybenzeneacetic acid), 4-hydroxy-3-methoxyphenylglycol (MHPG), homovanillic acid (HVA, 4-hydroxy-3-methoxyphenylacetic acid) and 3,4-dihydroxyphenylacetic acid (DOPAC) were between 5×10-9 and 4×10-8 M, using flow-injection analysis methodology. In addition, we demonstrate the rapid determination of homovanillic acid and 5-hydroxyindole-3-acetic acid in human urine – without the need for extraction procedures – using monolithic column chromatography with chemiluminescence detection.